Discourse Analysis of Emotional Expression in Dhruv’s “Double Take" - Fathur Ramadhan; Sysca Indriany (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study examines how emotional expression is represented in the song “Double Take” by Dhruv through a discourse analysis approach. The research focuses on four linguistic features; diction, metaphor, pronoun usage, and repetition and analyzes how these elements help convey emotional meaning in the lyrics. Using a qualitative descriptive method, the study analyzes official song lyrics as the primary data. The data were collected through documentation and interpreted using an interactive analysis model supported by theories from Geoffrey Leech, George Lakoff, Mark Johnson, Norman Fairclough, and Deborah Tannen. The findings identify 12 expressions of emotion represented through the four linguistic features. The study shows that diction reflects emotional honesty, longing, and inner conflict, while metaphors transform abstract feelings into imaginative expressions. Pronoun usage highlights interpersonal relationships and personal perspectives, and repetition strengthens emotional intensity and uncertainty. These linguistic features create complex emotional meanings, including vulnerability, obsession, and ambiguity. This analysis finds that emotional expression in song lyrics is shaped by the interaction of multiple linguistic elements rather than isolated features alone. The research contributes to discourse analysis by offering a better understanding of how language expresses subtle emotions in contemporary music and may serve as a reference for future studies in linguistics and literary analysis.